1995
DOI: 10.1111/j.1365-3083.1995.tb03626.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Reactivity to Hepatitis B Virus Vaccination and the Frequency of MHC Class I, II and III Alleles in Haemodialysis Patients

Abstract: To study the immunoreactivity genes in a heterogeneous human population needs a large number of individuals. Associations between HLA antigens and immunoresponse to viral or bacterial antigens have been studied with controversial results. As a homogeneous population, the MHC class I, II and III allele distribution was studied in 153 end-stage renal disease patients (ESRD, average duration of renal replacement: 8.2 + 5.1 years) immunized with a recombinant hepatitis B vaccine in accordance to the standard vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 11 publications
3
16
0
Order By: Relevance
“…Finally, in a very recent paper, Leonardi et al comparing a group of patient afected by diabetes mellitus type 1 (DMT1) and CD and a group afected by DMT1 without CD (both groups had similar HLA haplotype) found a higher nonsigniicant percentage of nonresponders in DMT1/CD group than in DMT1 (53.3% versus 38.2%); comparing the DMT1/CD group with CD group, the authors found a similar percentage (53.3% versus 50%) of nonresponders, and this result indirectly conirmed that gluten can favor a further decrease of eicacy to HBV vaccine, beyond the HLA system [29]. to the recombinant HBV vaccine [9,[30][31][32]. HLA is believed to contribute signiicantly to the genetic susceptibility immune response variations to the vaccine [33].…”
Section: Responses To Vaccinations In Celiac Childrensupporting
confidence: 67%
“…Finally, in a very recent paper, Leonardi et al comparing a group of patient afected by diabetes mellitus type 1 (DMT1) and CD and a group afected by DMT1 without CD (both groups had similar HLA haplotype) found a higher nonsigniicant percentage of nonresponders in DMT1/CD group than in DMT1 (53.3% versus 38.2%); comparing the DMT1/CD group with CD group, the authors found a similar percentage (53.3% versus 50%) of nonresponders, and this result indirectly conirmed that gluten can favor a further decrease of eicacy to HBV vaccine, beyond the HLA system [29]. to the recombinant HBV vaccine [9,[30][31][32]. HLA is believed to contribute signiicantly to the genetic susceptibility immune response variations to the vaccine [33].…”
Section: Responses To Vaccinations In Celiac Childrensupporting
confidence: 67%
“…Homozygous individuals for non-responder haplotype are strongly non-responsive to HBV vaccination when compared to the heterozygous state [45] . Homozygotes for HLA A1, B8, DR3, and DQ2 alleles are found exclusively in non-responders while heterozygotes are mostly nonresponders [46] for HBV vaccination. Non-uniformity observed in HLA association may be due to interaction between HLA factors within a haplotype.…”
Section: Response To Hbv Vaccinationmentioning
confidence: 99%
“…Previous studies have demonstrated that the HLA phenotype is considered the most important genetic marker of unresponsiveness to HBV vaccine. Homozygotes and heterozygotes for HLA-B8, DR3 and DQ2 were found to be exclusively in the nonresponder group with respect to responders (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…A seroconversion rate was defined by anti-HBs titers >10 IU/L. Patients with an anti-HBs titer <10 IU/L were regarded as unresponsive, between 10 and 100 IU/L as weakly responsive, and >100 IU/L as responsive (5).…”
Section: Determination Of Serum Anti-hbs Titersmentioning
confidence: 99%